Interferon Regulatory Factor 5 Mediates Lipopolysaccharide-Induced Neuroinflammation - Fan, Ziqi; Zhao, Shuai; Zhu, Yueli; Li, Zheyu; Liu, Zhirong; Yan, Yaping; Tian, Jun; Chen, Yanxing; Zhang, Baorong (Frontiers in Immunology, 2020)
Background: Activated microglia play a vital role in neuroinflammation in the central nervous system (CNS), which is associated with the pathogenesis and the progression of neurological diseases. Interferon regulatory factor 5 (IRF5) has been well established participating in inflammatory responses and is highly expressed in M1 macrophage in the periphery, the role of which in the CNS remains elusive. Methods: Lipopolysaccharide (LPS) was employed to induce neuroinflammation. Down-regulation of IRF5 in C57/BL6 mice and BV2 microglial cells were achieved by IRF5 siRNA transfection. The levels of pro-inflammatory cytokines were evaluated by ELISA and quantitative real-time PCR. The expression levels of IRF5 were examined by immunofluorescence and Western blot. Results: LPS induced significantly elevated expression of IRF5 in mouse brain, which co-localized with CD11b positive microglia. Down-regulation of IRF5 quenched the pro-inflammatory responses. The levels of pro-inflammatory cytokines TNF-α, IL-1β and IL-6 were up-regulated at 4 h after LPS treatment, which were significantly down-regulated with the knockdown of IRF5. LPS-induced pro-inflammatory responses were transient, which were comparable to control group at 24 h after LPS treatment. However, LPS did not up-regulate the expression of IRF5 in BV2 microglial cells, indicating that LPS-induced inflammation in BV2 cells does not involve IRF5 signaling. Conclusions: IRF5 mediates the inflammatory responses in the CNS, which might serve as a therapeutic target for CNS inflammatory diseases. LPS-induced inflammation does not involve IRF5 signaling in BV2 microglia.